PENDAMPINGAN MASYARAKAT DAN OPTIMALISASI PELAYANAN PEREKAMAN E-KTP MELALUI PENDEKATAN PARTISIPATIF DI KECAMATAN MEDANG DERAS - Flinderiva Sitorus; Martin Luter Purba (LPPM STAI Muhammadiyah Probolinggo, 2025)
Electronic Identity Card (E-KTP) recording services are a crucial part of population administration, ensuring legal certainty and fulfilling civil rights. In MEDANG Deras District, the implementation of E-KTP recording services still faces various challenges, such as limited facilities and infrastructure, technical equipment and network disruptions, and poor public understanding of service procedures and requirements. This community service initiative aims to improve the quality of E-KTP recording services through mentoring and direct community participation. The approach used is participatory, using qualitative descriptive methods through field observations, applicant assistance, and direct involvement in the administrative service process. Assistance is provided by explaining the service flow, assisting with document completion, and supporting officials in the population data recording process. The results of the activity indicate that mentoring and direct participation can improve public understanding, streamline the service process, reduce administrative errors, and increase the effectiveness of official work. This effort also encourages the creation of more orderly, responsive, and community-oriented services to support population administration at the sub-district level.